Domestic Violence in Assam: Socio-structural Dynamics. (September 2019) - Mahjebeen, Joanna
Conventional wisdom would have us believe that Assam is a state where the status of women is comparatively better off than that of their counterparts in the rest of India, that they suffer from fewer instances of domestic violence. The geographical contiguity of a region which contains some matrilineal tribal societies, significant female mobility, and a near absence of practices such as dowry or sati as part of tradition, might lend some credibility to this belief. However, present indicators and crime statistics have actually shown a high incidence of overall crimes against women in Assam. A complex socio-political milieu, characterised by increasing militarism and insurgency, continuing ethnic and group conflicts in an overall environment where 'market forces' dominate, has in its own way posed serious challenges to the security of women and led to the opening up of more and more 'violent spaces' –the home being one one of them. The present study endeavours to explore the socio-structural dynamics and contexts rooted in Assam that perpetuate domestic violence against women. The study underscores the necessity of informed policy-level interventions and a holistic approach to address structural constraints that underpin such violence.